Justice in the Balance: Activating Legislative-Reality Harmony to Ensure Fair Judicial Rulings Between Sharia And Modern Legal Systems - Chami, Yassine; Elsharef, Mohamed Elmadni; Qutieshat, Enas (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2026)
Achieving judicial fairness requires harmonizing legal texts with evolving societal realities. This research aims to explore the factors that enhance the fairness of judicial rulings by analyzing the interplay between abstract legal texts and practical reality. The method used involves a comparative analytical approach between modern legal systems and Islamic Sharia, supplemented by a review of judicial precedents. The results obtained indicate that legislative coherence and judicial discretion are critical for aligning rulings with justice objectives. Specifically, the study finds that rigid procedural adherence often undermines equity, whereas flexible interpretation grounded in contextual circumstances enhances fairness. Conclusions that can be drawn emphasize the necessity of developing legislative mechanisms that balance stability with equity, alongside promoting judicial transparency.